Homeland security: an introduction - Givens, Austen D. (Oxford University Press, 2022)
"This textbook will deliver a comprehensive, systematic introduction to homeland security today, including its conceptual foundations, legal underpinnings, historical evolution, constituent federal agencies, emerging technologies, and linkages to businesses, non-profits, civic groups, and individual citizens. Throughout the course of the book, particular emphasis will be placed on three paradigm shifts in homeland security: the new role of so-called "big data" analytics for risk assessment in homeland security decision-making; emerging understandings of the "homeland security enterprise," a term used by practitioners to describe whole-of-government efforts to manage natural and man-made threats; and the growing recognition of how international affairs can influence and shape domestic security considerations. The authors are all experts in homeland security and have published widely on the subject. In addition, the authors bring to bear on this project a compelling blend of academic and practitioner experience that will help this book to stand out among its competitors in the marketplace. Two of the authors (Busch and Givens) co-authored the 2014 book The Business of Counterterrorism: Public-Private Partnerships in Homeland Security. Alan Bers in has worked at the highest levels of the federal government, most recently as Assistant Secretary of International Affairs and Chief Diplomatic Officer at the OHS, and previously as Commissioner of U.S. Customs and Border Protection. Their combined expertise means that this project will benefit from both a rigorous scholarly approach and a compelling first-hand view of the federal government's inner workings from a former senior leader in the OHS. This project can be distinguished from other comparable textbooks, including those that focus upon specific sub-fields of homeland security. Some of these books offer introductions to homeland security but include little in the way of unifying themes or trends transcending the sub-fields of homeland security. Other books address specific problems in homeland security, such as terrorism or emergency management, and use these problems as starting points for broader discussions of government organizations involved in homeland security"--